The Effect of Working Capital and Profitability on Cash Holding in the Industrial Sector - Syifa, Rumaisya; Karim, Nazwa Fadilla; Leon, Farah Margaretha (International Journal of Accounting and Management Research, 2026)
Cash holdings of manufacturing companies in Indonesia varied during 2020-2024 in line with changes in investment policies, funding structures, and operating cash flows. This condition reflects the challenges companies face in maintaining optimal liquidity levels. The aim here is to search for the Effect of net working capital, profitability, leverage, cash flow, capital expenditure, and firm size on cash holding. This research implements a quantitative technique by the analysis of data regression through the FEM. This sample contains 39 manufacturing institutions/companies that existed in ISE with a total of 195 observations during the 2020-2024 period. The results show that Net Working Capital, Leverage, Cash Flow, and Capital Expenditure have an effect on Cash Holding, while Profitability has a significant negative effect on Cash Holding. These findings have implications for company management in formulating cash policies that are in line with liquidity management and investment decisions.